The Regulatory Effects of Interleukin-4 Receptor Signaling on Neutrophils in Type 2 Immune Responses - Egholm, Cecilie; Heeb, Lukas E. M.; Impellizzieri, Daniela; Boyman, Onur (Frontiers in Immunology, 2019)
Interleukin-4 (IL-4) receptor (IL-4R) signaling plays a pivotal role in type 2 immune responses. Type 2 immunity ensures several host-protective processes such as defense against helminth parasites and wound repair, however, type 2 immune responses also drive the pathogenesis of allergic diseases. Neutrophil granulocytes (neutrophils) have not traditionally been considered a part of type 2 immunity. While neutrophils might be beneficial in initiating a type 2 immune response, their involvement and activation is rather unwanted at later stages. This is evidenced by examples of type 2 immune responses where increased neutrophil responses are able to enhance immunity, however, at the cost of increased tissue damage. Recent studies have linked the type 2 cytokines IL-4 and IL-13 and their signaling via type I and type II IL-4Rs on neutrophils to inhibition of several neutrophil effector functions. This mechanism directly curtails neutrophil chemotaxis toward potent intermediary chemoattractants, inhibits the formation of neutrophil extracellular traps, and antagonizes the effects of granulocyte colony-stimulating factor on neutrophils. These effects are observed in both mouse and human neutrophils. Thus, we propose for type 2 immune responses that neutrophils are, as in other immune responses, the first non-resident cells to arrive at a site of inflammation or infection, thereby guiding and attracting other innate and adaptive immune cells; however, as soon as the type 2 cytokines IL-4 and IL-13 predominate, neutrophil recruitment, chemotaxis and effector functions are rapidly shut off by IL-4/IL-13-mediated IL-4R signaling in neutrophils to prevent them from damaging healthy tissues. Insight into this neutrophil checkpoint pathway will help understand regulation of neutrophilic type 2 inflammation and guide the design of targeted therapeutic approaches for modulating neutrophils during inflammation and neutropenia.